The Role of Interleukin-6 Family Members in Cardiovascular Diseases - Feng, Yongqi; Ye, Di; Wang, Zhen; Pan, Heng; Lu, Xiyi; Wang, Menglong; Xu, Yao; Yu, Junping; Zhang, Jishou; Zhao, Mengmeng; Xu, Shuwan; Pan, Wei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease is one of the main causes of human mortality. Cytokines play crucial roles in the development of cardiovascular disease. Interleukin (IL)-6 family members are a series of cytokines, including IL-6, IL-11, IL-30, IL-31, OSM, LIF, CNTF, CT-1, CT-2, and CLC, that regulate multiple biological effects. Experimental and clinical evidence shows that IL-6 family members are closely related to cardiovascular diseases such as atherosclerosis, hypertension, aortic dissection, cardiac fibrosis, and cardiomyopathy. This review mainly discusses the role of IL-6 family members in cardiovascular disease for the sake of identifying possible intervention targets for cardiovascular disease prevention and treatment.